The moderating role of good corporate governance on the relationship between corporate social responsibility and real earnings management - Sawssen Khlifi; Ghazi Zouari (Contabilitate şi Informatică de Gestiune, 2022)
Research Question: Does Good Corporate Governance have a moderating effect on the relationship between Corporate Social Responsibility and Real earnings management? Motivation: Nowadays, the relationship between responsible governance and REM has gained momentum in the accounting and financial studies. In this context, the present work will provide more insight into the relationship between responsible governance factors (GCG, CSR) and REM in the presence of R&D and M&A. Idea: this paper is to examine the moderating effect of good corporate governance (GCG) on the relationship between corporate social responsibility (CSR) and real earnings management (REM) level in innovative firms during mergers and acquisitions (M&A) transactions. Data: Using the corporate governance ratio and CSR scores calculated by the Thomson Reuters Eikon ASSET4 database, this study was developed to investigate these issues on a sample of 113 U.S. S&P 500 index firms between 2015 and 2021. This study adopted a sampling process that divides the total sample into two sub-samples according to whether the companies are involved in M&A transactions (test sample) or not (control sample). Tools: Multiple regressions on panel data is used to estimate our hypotheses. Findings: The empirical results reveal that CSR score has a negative and statistically significant effect on REM in highly R&D-intensive firms involved in M&A. Furthermore, the findings suggest that that good corporate governance variable plays a moderating role in the relationships between CSR and REM of these firms but not for the non-merged ones. Contribution: This research contributes to the literature by providing the significant links between some CSR, good corporate governance and the REM level within R&D-intensive firms in the American M&A market.